Artists and Writers for Two Centuries in the Cultural-Religious Context - Barbakadze , Ketevan; Gogoladze, Tamar ("Intercultural Dialogues" Transactions, 2021)
The history of Georgian painting is closely connected with the name of the 19th century artist Giorgi (Grigol) Maisuradze, who went through the way of demonstrating his artistic talent, from the family of peasants to the Brulov Academy and later working as a teacher of art. Giorgi Maisuradze's paintings are preserved in various museums in Kutaisi, and his following biography with his family and descendants still creates an interesting cultural gallery where famous Georgian artists, writers and scientists are presented. The artist's works has been thoroughly studied by an art critic Shalva Kvaskhkadze, and the present issue is from the history of Georgian culture.